Epidemiological aspect of rabies in the region of Vale do Paraiba during the period of 1992 to 2011 - Souza, M. C. A. M.; Torres Junior, M. D.; Ferreira, P. A. Lombardi; Nassar, A. F. C.; Villadobos, E. M. C.; Ferrari, J. J.; Lara, M. C. C. S. H.; Cunha, E. M. S. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Texto em inglês